Clinical Experience with SERPINA1 DNA Sequencing to Detect Alpha-1 Antitrypsin Deficiency - Maltais, François; Gaudreault, Nathalie; Racine, Christine; Thériault, Sébastien; Bossé, Yohan (Annals of the American Thoracic Society, 2018)
Diagnostic methods for AATD usually follow a multistep testing algorithm, including measuring serum alpha-1 antitrypsin levels, targeted genotyping toward the most common mutations, and phenotyping protease inhibitor with isoelectric focusing of serum alpha-1 antitrypsin (6, 7). Furthermore, each step has its own intrinsic limitations, creating further uncertainty in the interpretation of the results: 1) serum alpha-1 antitrypsin levels may be falsely elevated during acute inflammatory conditions (8); 2) commercially available genotyping tests are testing only the most common mutations, a major limitation considering that over 250 gene variants have been reported; and 3) protease inhibitor phenotyping only provides presumptive genotypes and characterizes a limited number of protein phenotypes. Discussion From this experience, we suggest a diagnostic scheme based on alpha-1 antitrypsin level, alone or supplemented with SERPINA1 DNA sequencing, depending on the presence or absence of clinical features associated with AATD (emphysema before 45 yr of age, predominant basal emphysema, positive family history, and associated liver disease or bronchiectasis; Figure 1). [...]DNA sequencing reveals the exact mechanism of the deficit, serves as a confirmatory diagnostic tool because the levels are not always reliable due to their intrinsic variability, and is necessary to investigate family members of the index case (7).